MAKNA LEKSIKAL DAN KULTURAL PADA TRADISI GERET SAPU DI DESA JAMBUWOK SERTA RELEVANSINYA DALAM PEMBELAJARAN BAHASA DAN SASTRA INDONESIA DI SEKOLAH MENENGAH ATAS - Elma Andini Fitriana (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
This study aims to describe the implementation of the tradition of Geret Sapu in Jambuwok Village, the lexical and cultural meaning of Geret Sapu, as well as the relevance of Geret Sapu's traditional study of Indonesian Language and Literature learning in Senior High Schools. In this study took the tradition of Geret Sapu in Jambuwok Village, Mojokerto Regency. Research data can be obtained using documentation and interview methods. The subjects in this study were the Jambuwok Village community. The type of research used in this study uses qualitative descriptive research methods. Data validation techniques used are triangulation of data sources and methods. There are three data analysis techniques used, namely, data reduction, data verification, and data display. The results of the study indicate that there are two processes in the implementation of Geret Sapu tradition in Jambuwok Village. The first process is preparation and the second process is implementation. The form of goods in Geret Sapu carried out in Jambuwok Village has six forms which include broom sticks, jugs, mats, pillows, bolsters, and soil. The meaning of semantic aspects is analyzed using lexical meaning and cultural meaning. Geret Sapu tradition studies can be used as a relevance to the learning of Indonesian Language and Literature in High School, namely as a reference for teaching materials. Keywords: Ethnolinguistics, Geret Sapu Tradition, Indonesian Language and Literature Learning in High School.